Occurrance and antibiotic resistance of Campylobacter jejuni and Campylobacter coli in retail broiler chicken - M. R., Usha; Maarof, Fauziah; Robin, Tunung; Chai, Lay Ching; Cheah, Yoke Kqueen; Mohamad Ghazali, Farinazleen; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Broiler part samples (80 fresh and 80 chilled) were examined for the prevalence and numbers of C. jejuni and C. coli by employing most-probable-number (MPN) and polymerase chain reaction (PCR) techniques. The prevalence of the bacteria was high where C. jejuni was detected in 92.5% fresh and 53.8% chilled samples while C. coli in 80.0% fresh and 56.3% chilled. The number of these bacteria in the positive fresh and chilled samples was from 3 to more than 2400 MPN/g and from 3 to 290 MPN/g, respectively. Antibiotic resistance test (using Kirby-Bauer disc diffusion method) on 10 C. jejuni and 13 C. coli isolates toward ampicillin, tobramycin, enrofloxacin, ciprofloxacin, tetracycline, cephalothin, gentamicin and norfloxacin revealed high resistance toward all antibiotics (20.0% - 100.0%). All isolates were resistant to at least two antibiotics. This study highlights the potential of multidrug-resistant C. jejuni and C. coli transmission to humans through fresh and chilled broiler parts. Consecutive studies with bigger sample sizes and covering all over Malaysia are warranted in future.